VAGINAL LEIOMYOMA IN A PREGNANT BITCH - UMAMAGESWARI, J; SRIDEVI, P; RANGASAMY, S; SRIDHAR, R (The Indian Journal of Animal Reproduction, 2016)
A five-year-old pregnant bitch presented with the history of foul smelling vaginal discharge since two days was examined. Grossly, a pinkish round, solid, pedunculated mass was detected in the posterior vaginal wall which was confirmed as leiomyoma upon histopathology. The vaginal mass dropped off on its own and the bitch whelped live puppies by assisted delivery. Ovariohysterectomy was recommended to prevent recurrence.
Keywords: Bitch; Canine; Pregnancy; Vaginal leiomyoma; Vaginal mass